Upaya Pencegahan HIV pada Remaja melalui Edukasi di Posrem Eirin Kota Jambi - Kusuma, Ratu (Universitas Baiturrahim, 2025)
Adolescent health is a global problem, including the risk of contracting HIV. BPS 2018 recorded 86,780 cumulative cases of HIV/AIDS and some occurred in teenagers. IDAI reports that in 2022 there will be 741 adolescents aged 15-19 years infected with HIV and 172 cases will occur at ages ≤ 14 years. The 2020 Jambi Province Health Profile recorded 169 new cases of HIV and 32 new cases of AIDS in Jambi Province, the most cases in Jambi City (122 HIV and 28 AIDS). Data from the ODHA Community (Yayasan Kanti Sehati Sejati Kota Jambi) for 2022 recorded 1115 ODHA in Jambi Province. Therefore, it is necessary to provide education through activities of community service. This activity was carried out in the working area of the Putri Ayu Health Center, Jambi City because based on the HIV/AIDS and IMS Program Medical Records in 2023 there were 92 cases of HIV/AIDS, and in 2020 there was 1 male teenager infected with HIV. Data from Yayasan Kanti Sehati Sejati notes that in the last 1 year (2021-2022) several new cases were adolescent ODHA (aged 16-20 years) and 1 of them was even infected at the age of 14 years. Education was carried out on July 15 2023 at the homes of residents of RT 15 Sungai Putri Sub-district for 34 young men and women from Posrem Eirin who are members of Posrem Senja Danau Sipin. The material is delivered via power point for ± 60 minutes including a question and answer and sharing session. Before and after education, a pretest and posttest were carried out using the same questionnaire. After being given education, there was an increase in the average knowledge of 2.0 and attitude of 4.5 points. Thus, it is concluded that the knowledge of teenagers at Posrem Eirin about HIV is not optimal.